Extracellular vesicles for cancer therapy: potential, progress, and clinical challenges - Ren, Lili; Zhang, Dingmei; Pang, Long; Liu, Shiyu (Frontiers in Bioengineering and Biotechnology, 2024)
Extracellular vesicles (EVs) play an important role in normal life activities and disease treatment. In recent years, there have been abundant relevant studies focusing on EVs for cancer therapy and showing good performance on tumor inhibition. To enhance the effectiveness of EVs, EV analogs have been developed. This review summarizes the classification, origin, production, purification, modification, drug loading and cancer treatment applications of EVs and their analogs. Also, the characteristics of technologies involved are analyzed, which provides the basis for the development and application of biogenic vesicle-based drug delivery platform for cancer therapy. Meanwhile, challenges in translating these vesicles into clinic, such as limited sources, lack of production standards, and insufficient targeting and effectiveness are discussed. With ongoing exploration and clinical studies, EV-based drugs will make great contributions to cancer therapy.